2011
DOI: 10.1002/lary.22197
|View full text |Cite
|
Sign up to set email alerts
|

OtoscopySimulation: A New Paradigm in Undergraduate Medical Education

Abstract: Otologic complaints are among the most common causes of medical consultation worldwide, especially in children. Only 5% of medical students at the end of their Clerkship feel that they could consistently perform a reasonable otoscopic examination (Jones et al., Pediatr Res. 2003;53(suppl):95A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…To this effect, the Department of Otolaryngology–Head and Neck Surgery, in collaboration with MaRS Innovation Center (Toronto, Canada), developed an innovative otoscopy teaching tool, the OtoSim, which is capable of accurately simulating the manual techniques of otoscopy and illustrating images of normal and pathological anatomy of the ear through the otoscope. Although the otoscopy simulator has been proven to be a powerful tool for improving the diagnostic accuracy of medical students when used in small group settings, it has not yet been evaluated in a large‐scale training session …”
Section: Introductionmentioning
confidence: 99%
“…To this effect, the Department of Otolaryngology–Head and Neck Surgery, in collaboration with MaRS Innovation Center (Toronto, Canada), developed an innovative otoscopy teaching tool, the OtoSim, which is capable of accurately simulating the manual techniques of otoscopy and illustrating images of normal and pathological anatomy of the ear through the otoscope. Although the otoscopy simulator has been proven to be a powerful tool for improving the diagnostic accuracy of medical students when used in small group settings, it has not yet been evaluated in a large‐scale training session …”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of physical simulators as a trainingaid for teaching otoscopy skills mainly used post-intervention test/performance within the simulated setting and all studies found a positive effect on diagnostic skills. 1,[12][13][14][15][16][17] One study, aiming at gathering validity evidence for a new digital otoscopy training model, only evaluated the participants' opinion on the training model, which cannot be considered a learning outcome or contributing to validity of the model. 11 Three studies investigated transfer to real-life patients.…”
Section: Physical Simulatorsmentioning
confidence: 99%
“…1a). Initiatives through non-specialist publications [8] and teaching materials [9] should help promote awareness. These features may be revealed by pneumatic otoscopy or gentle probing, but are unlikely to be demonstrable in smaller lesions or smaller children.…”
Section: Consider Characteristics Allowing Identificationmentioning
confidence: 99%